Energia solar fotovoltaica: estudo de caso, viabilidade técnica e financeira para atendimento de prédio comercial em Tucuruí - PA - SILVA, Lyandra Araújo da (2023)
As the environmental crisis intensifies and electricity consumption increases, the search for sustainable energy consumption from renewable sources is growing. Electricity consumption has been increasing with economic growth, new energy technologies and the expanding Brazilian population. Faced with this crisis situation, more and more electricity is needed throughout the year to meet demand. In this sense, solar energy is an excellent alternative for clean, silent, almost pollution-free, inexhaustible energy, with a variety of materials and adaptable to different projects. The work presented here involves the design and installation of a photovoltaic system connected to the grid for the production of electricity in a commercial establishment located in the municipality of Tucuruí, in the state of Pará. Where the installation site data were first collected. From there, the total coverage area and the consumption of the relevant building for the sizing of the photovoltaic system were analyzed. In this way, in addition to estimating the annual energy produced by the system, it is possible to size and specify the modules and inverters, making it possible to install the project more effectively on site.